Trends in routine screening examinations. - Dawson, D A (1987)
Data from the 1973 and 1982 National Health Interview Surveys reveal increased use of routine medical examinations between the two survey dates. The proportion of adults age 40 or older who ever had a glaucoma test increased by 50 per cent. Other large increases were in the proportion of adults age 40 or older who ever had an electrocardiogram and in the proportions of women age 17 or older who ever had breast examinations or Pap smears.